Spatiotemporal Analysis of Glacier Movement on Muztagh Peak Based on Hybrid Cloud Remote Sensing - Xu, Litao (International Journal of Natural Resources and Environmental Studies, 2026)
Global warming is accelerating glacier dynamics in High Mountain Asia, which underscores the importance of high-precision monitoring for regional water security. This study investigates the surface velocity of the Muztagh Ata glacier group through a joint observation framework. We utilize the ASF-HyP3 cloud platform for efficient SAR preprocessing via the ISCE2 processor and MintPy for time-series InSAR inversion. By incorporating ERA5 meteorological data for tropospheric correction and performing geometric decomposition on multi-orbit Sentinel-1 data, we identify a radial flow pattern with peak horizontal velocities of approximately −2.0 m/year.